Review of the structural and functional brain changes associated with chronic kidney disease - Michna, Martin; Kovářová, Lucie; Valeriánová, Anna; Malíková, Hana; Weichet, Jiří; Malík, Jan (Physiological research, 2020)
Chronic kidney disease (CKD) leads to profound metabolic and hemodynamic changes, which damage other organs, such as heart and brain. The brain abnormalities and cognitive deficit progress with the severity of the CKD and are mostly expressed among hemodialysis patients. They have great socio-economic impact. In this review, we present the current knowledge of involved mechanisms.
Keywords: rizikové faktory; Cognition Disorders; Animals; Renal Insufficiency, Chronic; Risk Factors; lidé; zvířata; Brain; kognitivní poruchy; mozek; chronická renální insuficience; Humans